Reporting Child Exposure to Domestic Violence: Pre-Service Teachers’ Attitudes and Behaviours - Vink, Katherine (2014)
The present study examined pre-service teachers’ attitudes and behaviours toward reporting child exposure to domestic violence. Domestic violence exposure is defined as being within sight or sound of violence (Edleson et al., 2007). Due to their daily contact, teachers are in a unique position of being able to recognize children who are exposed to domestic violence, as they are amongst the first individuals to recognize warning signs and changes in behaviour including appearance, attitude, and academic performance (Byrne & Taylor, 2007). A sample of 190 University of Western Ontario Bachelor of Education students completed a questionnaire measuring attitudes and beliefs toward domestic violence, as well as intervention intentions in cases of child exposure to domestic violence. The present study evaluated the questionnaire by focusing on four major components: (1) pre-service teachers’ underlying attitudes toward violence against women, (2) the behaviours pre-service teachers consider to constitute as domestic violence, and how serious they believe them to be, (3) pre-service teachers’ likelihood to intervene in cases of suspected child exposure to domestic violence, and the avenues through which they respond to such cases, and (4) the influence of past experiences on pre-service teachers’ reporting behaviours